Supporting recovery, healing and wellbeing with Aboriginal communities of the southeast coast of Australia: a practice-based study of an Aboriginal community-controlled health organisation's response to cumulative disasters - Lynne Keevers; Maria Mackay; Sue-Anne Cutmore; Kristine Falzon; Summer May Finlay; Samantha Lukey; Julaine Allan; Chris Degeling; Ruth Everingham; Mim Fox; Padmini Pai; Katarzyna Olcon (BMC, 2024)
Abstract Background The recent crises of bushfires, floods, and the COVID-19 pandemic on the southeast coast of Australia were unprecedented in their extent and intensity. Few studies have investigated responses to cumulative disasters in First Nations communities, despite acknowledgement that these crises disproportionately impact First Nations people. This study was conducted by Aboriginal and non-Aboriginal researchers in partnership with Waminda, South Coast Women's Health and Wellbeing Aboriginal Corporation, an Aboriginal Community Controlled Health Organisation (ACCHO). It investigated the collective experiences of people affected by cumulative disasters to identify the practices that support healing, and recovery for Aboriginal communities. The study addresses a knowledge gap of how Waminda, designs, manages and delivers responses to address complex health and social issues in the context of cumulative disasters. Methods Underpinned by practice theory this study employed Indigenous-informed, narrative inquiry. Culturally-appropriate, multiple interpretive methods were used to collect data including: observations; yarns with Aboriginal community members, yarns with Waminda practitioners, management and board members; interviews-to-the-double, visual images and documentation. The data were collated and analysed using the phases of reflexive thematic analysis. Results The paper articulates a suite of culturally safe and place-based practices that enhance social, emotional and spiritual well-being following cumulative disasters. These practice bundles include: adopting a Country-centred conception of local communities; being community-led; viewing care as a collective, relational, sociomaterial accomplishment and having fluid boundaries. These practice bundles 'hang together' through organising practices including the Waminda Model of Care, staff wellbeing framework and emergency management plan which orient action and manage risks. The paper demonstrates the need for disaster responses to be community-led and culturally situated. ACCHOs are shown to play a crucial role, and their local responses to immediate community needs are grounded in contextual knowledge and use existing resources rather than relying on mainstream system-wide interventions. Conclusions The paper suggests crafting responses that focus on assisting communities (re)gain their sense of belonging, hope for the future, control over their lives and their capacities to care for and to be cared for by Country, are key to both enhancing healing, health and well-being and harnessing the strengths of communities.